Dynamics of X-ray emission from a small plasma focus - Wong, C.S.; Moo, S.P.; Singh, J.; Choi, P.; Dumitrescu-Zoita, C.; Silawatshananai, C. (Malaysian Journal of Science, 1996)
The dynamics of X-ray emission from a 3 kJ argon plasma focus has been studied using a five channel PIN diode X-ray spectrometer (DXS) and a time-resolved X-ray pinhole imaging system. The five channel DXS is used to investigate the spectral evolution of the X-ray emission from the focussed plasma whereas the time-resolved X-ray pinhole imaging system provides information on the temporal evolution of the structure, of the X-ray emission regions during the focus discharge. Two periods of X-ray emission are observed during a focus discharge, one during the radial compression phase of the discharge and the second period occurs at a time of about 200 ns after the maximum compression. The first period X-rays are emitted from a hot argon plasma with an electron temperature of about 1.5 keV whereas the second period X-rays consist of predominantly the copper Ka line radiations. Time-resolved X-ray pinhole imaging of the focus discharge visualises the formation of the focussed plasma column during the radial compression phase corresponding to the first period of X-ray emission. The formation of a second compression at a time of about 65 ns after the first maximum compression has also been observed. The second period X-ray emission is observed at a time of about 200 ns from the maximum compression and it is believed to be emitted from the anode itself or from the copper vapour ejected from the anode due to electrori'beam bombardment.